Alchemy of secrets : a novel [large type] - Garber, Stephanie (Thorndike Press large print high octane., 2025)
"It starts with a class in an old movie theater. Folklore 517: Local Legends and Urban Myths, taught by a woman called the Professor. Most students believe the Professor's stories are just fiction, but Holland St. James has always been convinced that magic is real. When she tracks down a local legend named the Watch Man, who can supposedly tell you when you'll die, the world finally makes sense. Except that the Watch Man tells her she will die at midnight tomorrow unless she finds an ancient object called the Alchemical Heart. With the clock ticking, Holland is pulled deeper into this magical world inthe heart of Los Angeles--and into the path of a magnetic stranger"--